Pertanggungjawaban Hukum Dalam Kasus Perjanjian Pinjam Nama Pada Fitur Shopee Pinjam - Amia Eka Putri; Suraji Suraji (Lembaga Pengembangan Kinerja Dosen, 2024)
Technological developments have given rise to various new innovations to make it easier to fulfill human needs, one of which is online lending and borrowing services. Shopee Pinjam or SPinjam is an example of an online loan service that includes standard clauses in the contract agreed by the debtor. The problem that often occurs due to easy access to borrowing and lending through SPinjam is misuse of data for other people's needs or what is known as name lending. The purpose of writing this research is to find out how legal accountability is given to the parties. The research method used is a normative research method, with deduction analysis techniques. The results of this research indicate that the name borrowing agreement made between the name borrower and the name giver is an oral agreement that has weak legal force. This agreement is only binding on the party making it without any intervention from SPinjam. Legal responsibility regarding the repayment of SPinjam is an absolute responsibility that must be fulfilled by the debtor who agrees. The name borrower cannot be burdened with legal responsibility because the name borrowing agreement has not been specifically regulated in positive law in Indonesia so that the solution to the problem that can be done is by deliberation between the name borrower and the name giver.